(3TQM GdZehV aj eSGFd GdYQhVs - (3CHh GdMSf Ydj Hf eMeO Hf Ydj Hf GdMSf Hf HQis; (3GHf GdSbGW , CHh YHO Gddgs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO NGJe GdfHjf , HOC QMeg Gddg cJGHg HGdMeO JHQckG HaVjdJg cGf Gddg JYGdi EHJOC Hg cJGHg hLYdg BNQ OYGA Cgd LfJg ceG bGd JYGdi (B( (3hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf (B) s
(3BNQgG (B:s
(3hbhd BNQ GdYjf dgG Oe hOeY Je cJGH TQM GdZehV ef eSGFd GdYQhV s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B6s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais